Pengembangan Media Pembelajaran Interaktif Dasar Listrik dan Elektronika menggunakan Aplikasi Lectora Inspire - Nurul Muflia; Hambali Hambali (Jurnal Pendidikan Teknik Elektro, 2021)
This study discusses the development of learning media using Lectora Inspire for study Basic of Electrics and Electronics in SMK Negeri 1 Padang. The purpose of this research is to develop interactive learning media for study Basic of Electrics and Electronics at X grade of SMK Negeri 1 Padang. The type of research used is Research and Development. The subject of this research is interactive learning media using the Lectora Inspire for subject study DLE (Basic of Electrics and Electronics). Student of X grade TJTL class in SMK Negeri 1 Padang and one teacher of DLE study as respondents. The development model used in this research is a 4-D development model, that has four steps are Define, Design, Develop and Disseminate. The result of media validation has an average score by all of the validator team is 0.82. The practicality test of interactive learning media by the teacher had a result is 89.58% in the practical category and the practicality test result from 18 students is 82.37% were included in the practical category. And the interactive learning media can be used for Basic Electrics and Electronics Study.